Role of Neutrophils Extracellular Traps in Acute kidney injury - Neama Ahmed Abd El-Aziz,; Hesham Abd El Halim,; Hesham Kamal Habeeb Keryakos,; Amel Mahmoud Kamal El-din, (International Journal of Medical Toxicology and Legal Medicine, 2024)
Acute kidney injury (AKI) results in the abrupt loss of kidney function, leading to the retention of waste products, electrolyte disturbances, and volume status changes. The term AKI has replaced acute renal failure because smaller changes in kidney function without overt failure can result in significant clinical consequences and increased morbidity and mortality. Changes in kidney function are detected by a change in biomarkers, the most common biomarker being serum creatinine (SCr). Serum creatinine is an imperfect biomarker for recognizing AKI, given that an increase in SCr often lags (48–72 hours) behind the onset of injury. So, we are searching for a new biomarker for AKI as Uncontrolled inflammatory and immune responses are often involved in the development of acute and chronic forms of renal injury. Neutrophils are innate immune cells recruited early to sites of inflammation, where they produce pro-inflammatory cytokines and release mesh-like structures comprised of DNA and granular proteins known as neutrophil extracellular traps (NETs), which are potentially toxic, contribute to glomerular injury, activate autoimmune processes, induce vascular damage, and promote kidney fibrosis. Evidence from multiple studies suggests that an imbalance between production and clearance of NETs is detrimental for renal health. So many studies aimed at modulating NET-associated processes could have a therapeutic impact on a plenty of inflammatory diseases that target the kidney. In this article we summarize the role of NETs in the pathogenesis of acute kidney injury and their mechanisms of tissue damage.